POLA KOMUNIKASI DAKWAH DALAM PENYIARAN ISLAM BERBASIS KEARIFAN LOKAL (STUDY DAKWAH TENTANG BUYA HAMKA) - Muhammad Al Fauzan (JURNAL SYIAR-SYIAR, 2023)
ABSTRACTMuhammad Al Fauzan, NPM 180015 (2022). Communication Patterns of Da'wah in Islamic Broadcasting Based on Local Wisdom (Da'wah Study on Buya Hamka) This study aims to determine the communication patterns of da'wah carried out by Buya Hamka and to find out the implementation of the elements of da'wah by Buya Hamka. Data collection was carried out by using literature study references. In reviewing the data using descriptive exploratory method. The results showed that the da'wah principle uses the principle of rationality, has firmness in holding Islamic principles and has exemplary, and Hamka's da'wah has a great effect on the community, one of which is increasing religious knowledge, increasing belief and faith, providing enlightenment to the people and changing behavior into even better.Keywords: Buya Hamka, Principles of Da'wah, Elements of Da'wah